Pengaruh Social Media Marketing terhadap Loyalitas Konsumen E-Commerce melalui Brand Image dan Relationship Marketing - Danny Khairul (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2021)
The purpose of this paper is to empirically investigate the influence of social media marketing towards brand image and relationship marketing in the Indonesian e-commerce context. The proposed model also aims to examine the relationship between social media marketing, brand image, satisfaction, trust and loyalty. The e-commerce industry in Indonesia is experiencing very tough competition with many emerging platforms. E-commerce industry players must be able to implement strategies to increase consumer loyalty, in order to compete in this industry. The strategy that can be done is by doing social media marketing activities. This is because the Indonesian people are very active in using the internet and social media, so this phenomenon opens up opportunities for business people, especially in the e-commerce industry. Objects in this study addressed to e-commerce consumer in Indonesia. A total of 200 respondents have been obtained throught the distribution of questionnaires by using the method of non-probability sampling. The study model was estimated by using structural equation modelling with LISREL 8.8. The results showed that social media marketing has a significant effect on brand image and trust. Satisfaction and trust have a significant effect on loyalty. Furthermore, brand image has a significant effect on satisfaction, and satisfaction has a significant effect on trust. By contrast, social media marketing has no significant effect on satisfaction, and brand image has no significant effect on loyalty. This study concluded that to increase consumer loyalty in e-commerce, industry players must be able to improve the accuracy of product description suitability, increase responsiveness to complaints and input given by consumers, and increase marketing activities through social media. Keywords: brand image, e-commerce, loyalty, relationship marketing, social media marketing